Burnout in nursing personnel in a regional university hospital - Moustaka, Eleni; Malliarou, Maria; Konstantinidis, Theodore; Manolidou, Zacharoula; Sarafis, Pavlos (My University, 2009)
Abstract: In this study we aimed to investigate the frequency of the burnout syndrome among the nursing personnel of all rungs. The present study is descriptive with synchronical comparisons and cross-correlations. The research was conducted in a Regional University Hospital. Subjects: The questionnaire was distributed to 150 RNs and NAs and the response rate was 42,6% (N=64). Main outcome measure is the determination of the burnout levels of nurses employed in a major Regional University hospital and the correlation of factors of burnout level with demographic and job related factors. Results: Generally occupational burnout appears to be in moderate levels. 9,37% of the sample experienced a high degree of burnout while 6,24% experienced low degree. 34,38% of the sample experienced low emotional exhaustion, 20,31% moderate and 45,31% high. 37,5% of the sample experienced low personal accomplishments, 28,13% moderate, 34,38% high. 26,54% of the sample experienced low depersonalization, 32,81% moderate, 40,63% high. Emotional exhaustion correlates significantly with working a rotation shift (p=0,05). Emotional exhaustion correlates significantly with resignation from hospital (p=0,002). Depersonalization correlates significantly with the multidisciplinary cooperation (p=0,05). The factors of burnout were examined in combination with the qualitative characteristics, as sex, the marital status, the level of education, with ?2 and in combination with the quantitative demographic characteristics as the age, the weight, the height, the number of children; with ANOVA oneway and it did not find to relate themselves considerably.
Keywords: Burnout; Registered nurse; Nurse assistant; Regional hospital; Maslach burnout inventory